2007
DOI: 10.1007/s11630-007-0301-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tapered diffuser vane on the flow field and noise of a centrifugal compressor

Abstract: The effects of a three-dimensional tapered diffuser vane on the flow field and noise radiated from a centrifugal compressor are investigated by both CFD analyses and experiments. Tapered diffuser vanes are very useful not only for the reduction of the interaction tone noise but also for the improvement of the pressure recovery characteristics within the diffuser passage. By using tapered diffuser vanes, the interaction area between the impeller-discharge flow and diffuser vanes becomes small, and then the nois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The inlet and outlet diameters of the impeller are 248 mm and 328 mm, respectively. Please refer to our previous papers for details of the tested compressor [5] .…”
Section: Experimental Apparatus and Proceduresmentioning
confidence: 99%
“…The inlet and outlet diameters of the impeller are 248 mm and 328 mm, respectively. Please refer to our previous papers for details of the tested compressor [5] .…”
Section: Experimental Apparatus and Proceduresmentioning
confidence: 99%
“…Meanwhile, the ILEVD extends the operating range. The work by Ohta et al [10] showed that the tapered diffuser vane could remarkably reduce the compressor noise, whereas it diminished the pressure rise and working range.…”
Section: Influence Of Vaned Diffuser With Broken Leading Edgementioning
confidence: 99%
“…In the previous studies of the centrifugal compressor stage, some researchers [6,7] considered that the optimal impeller-diffuser radial gap existed, and they advised that the optimal value of diffuser leading edge radius, R 3 /R 2 , was from 1.06 to 1. 10. The impeller-diffuser radial gap of the vacuum fan is very small, which leads to the strong interaction between the flow discharged from the impeller exit and the diffuser.…”
Section: Introductionmentioning
confidence: 99%
“…Ohta et al. 6,7 designed three types of tapered diffusers with different tapered portion lengths on the pressure and suction surfaces. All three types of tapered diffusers were effective in reducing the noise level, and the application of diffuser type C (i.e.…”
Section: Introductionmentioning
confidence: 99%